Pelatihan Kewirausahaan Bagi Karang Taruna Dalam Memanfaatkan Hasil Lahan Pekarangan Rumah Di Dusun Ketapang Desa Batu Putih Kecamatan Sekotong Kabupaten Lombok Barat - Suryaningsih; Iswan; Dhea Chandra Dewi; Nurwahidah (CV. Multi Kreasi Media, 2024)
This community service was carried out in Ketapang Hamlet, Batu Putih Village, Sekotong District, where the youth organization and mothers are the partners in this activity. The purpose of this community service is to provide training and skills to young men and women of the youth organization so that they have the skills, knowledge and attitudes in entering the world of independent entrepreneurship and applying the knowledge gained in their lives. The method used in this service is to provide various types of training and product processing in an effort to utilize the results of the home-based agricultural land which aims for business independence in an effort to increase the community's economic income. The forms of training that we provide include making salted eggs using the soaking method without ash using only salt water, processing basic banana ingredients into light snacks with various flavors, making traditional cakes made from cassava and coconut so that they have an attractive taste and appearance. The results of this service are that training participant partners are able to implement the results of the training as provisions so that they can become entrepreneurs and have skills.